Mesenchymal stem cell-derived extracellular vesicles in systemic sclerosis: role and therapeutic directions - Wang, Xuan; Guo, Jiaying; Dai, Qiangfu (Frontiers in Cell and Developmental Biology, 2024)
Systemic sclerosis (SSc) is a complex autoimmune disease with clinical symptoms of vascular damage, immune disorders, and fibrosis, presenting significant treatment challenges and limited therapeutic options. Mesenchymal stem cell-derived extracellular vesicles (MSC-EVs) have been demonstrated in numerous studies as more effective than MSCs in treating autoimmune diseases. Recent studies demonstrate that MSC-EVs can significantly ameliorate the symptoms of SSc and mitigate pathological changes such as vascular injury, immune dysregulation, and fibrosis. These findings underscore the promising therapeutic potential of MSC-EVs in the treatment of SSc. MSC-EVs promote angiogenesis, modulate immune dysfunction, and combat fibrosis. This article summarizes the therapeutic applications and possible mechanisms of MSC-EVs for SSc, thereby offering a novel therapeutic direction for the treatment of SSc.